Sistem Pendukung Keputusan Pemilihan Apoteker Terbaik Pada PT. Kimia Farma (Persero) Tbk Medan Menerapkan Metode Vikor - Kusuma, Ardi; Ginting, Garuda (Jurnal Sistem Komputer dan Informatika (JSON), 2020)
Pharmacists are professional workers who have basic education and skills in the field of pharmacy and are given the authority and responsibility to carry out pharmaceutical work. In the pharmaceutical industry, both those that have been operating and are about to be established, there must be at least 3 (three) Indonesian pharmacists. Decision Support System (SPK) has the aim of providing predictions, providing information and directing information users to be able to make decisions more effectively. Decision Support System (SPK) applications use a flexible, interactive and adaptable CBIS (Computer Based Information System) that was developed to support solutions to specific unstructured management problems. The VIKOR method is used to overcome the problem of complex multi-criteria systems that focus on ranking and selection of alternatives. The first proposed procedure calculates the ideal and negative solutions by considering the criteria and weights of each alternative, and the corresponding utility.